Determinants of essential newborn care for institutional births in Bangladesh: Findings from the 2019 MICS Survey - Syeda Sumaiya Efa; Syed Nafi Mahdee; Md Fuad Al Fidah (Global Pediatrics)
Background: Millions of newborns die globally during the neonatal period. Essential newborn care (ENC) is designed to lower neonatal morbidity and mortality. The current study investigated the association between sociodemographic, antenatal, and delivery care factors that may impact ENC practices for institutional birth in Bangladesh. Methods: The current study utilized publicly available, nationally representative data. A total of 404 participants were considered for analysis. A logistic regression model was developed, with significant variables identified by chi-square tests. A p-value <0.05 was considered statistically significant (α=0.05). Results: Almost half of the participants were <20 years old (241, 59.7 %), half had secondary level education (205, 50.7 %), and one-third were from the poorest wealth quintile (123, 30.4 %). The prevalence of proper ENC was 57 (14.1 %). In 383 (94.8 %) cases, instruments were utilized to cut the umbilical cord, with 271 (67.1 %) showing no application of substances to the cord stump. Following birth, 396 (98.0 %) newborns underwent drying, while 294 (72.8 %) were immediately wrapped. Delayed bathing was observed in 131 (32.4 %) cases, with 359 (89.9 %) initiating breastfeeding. Proper ENC was associated with assistance by skilled birth attendant (SBA) (p = 0.004) and residence (p = 0.047). Higher odds of proper ENC were found among those who received assistance by SBA (AOR: 2.39; 95 % CI: 1.32–4.32; p = 0.004) and belonging to the middle class (AOR: 2.90; 95 % CI: 1.26–6.68; p-value=0.012). Conclusion: Proper ENC in institutional birth is not widely practiced in Bangladesh. Targeted health promotional activities and policies, especially assistance by a SBA and raising awareness among mothers of the poorest families, can help to improve ENC practices during institutional birth.